Effect of Egg and Milk Supplement on Breast Milk Volume at 48 and 72 Hours Postpartum: A Randomized-Controlled Trial - Jullapong Achalapong (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objective:To determine whether egg and milk supplement with regular diet can increase breast milk volume at 48 and 72 hours postpartum.Materials and Methods: A randomized-controlled trial was conducted at Chiangrai Prachanukroh Hospital between January 2013 and December 2013. One hundred and twenty term pregnant women with spontaneous vaginal delivery were randomized into four groups to receive (1) regular postpartum diet, (2) regular diet with milk supplement, (3) regular diet with egg supplement, or (4) regular diet with egg and milk supplement three meals a day. Breast milk volume was measured using an electric breast pump for 15 minutes for each breast at 48 and 72 hours postpartum. The differences in breast milk volume at 48 and 72 hours postpartum between groups were assessed using an analysis of covariance adjusted for the variables significantly different between groups at the time of delivery. Results:Age of postpartum mothers (p=0.039) and experience of breastfeeding (p=0.045) were significantly different between groups, but not body mass index, gestational age at delivery and infant birth weight. In the analysis of covariance adjusted for maternal age and breastfeeding experience, postpartum mothers who received a regular diet with egg and milk supplement had a significantly higher volume of breast milk at 48 and 72 hours compared to mothers who received a regular diet (p<0.001).Conclusion: A diet with both egg and milk supplement three meals a day significantly increased breast milk volume in lactating women.